2009
DOI: 10.1016/j.juro.2009.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Transition Zone Directed Needle Biopsies Uncommonly Sample Clinically Relevant Transition Zone Tumors

Abstract: Cancer identified in transition zone directed needle biopsy cores was not from the transition zone or did not reflect a dominant transition zone lesion in almost 80% of cases. Cancer identified in a left or right transition zone directed needle biopsy did not predict ipsilateral transition zone cancer in almost 50% of cases. These findings suggest that such biopsies do not adequately characterize transition zone tumors. Thus, care should be taken in their interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Haarer et al analyzed RP findings in 61 PCa cases diagnosed by TZ directed biopsies. 30 Cancers identified by these cores were not from the TZ and these biopsies did not reflect a dominant TZ lesion in almost 80% of cases. 3) The urologist was not blinded to MRI positive lesions before SB, which likely could have biased results.…”
Section: Discussionmentioning
confidence: 93%
“…Haarer et al analyzed RP findings in 61 PCa cases diagnosed by TZ directed biopsies. 30 Cancers identified by these cores were not from the TZ and these biopsies did not reflect a dominant TZ lesion in almost 80% of cases. 3) The urologist was not blinded to MRI positive lesions before SB, which likely could have biased results.…”
Section: Discussionmentioning
confidence: 93%
“…23 Cancer concordance of transition-zone biopsies and prostatectomy specimens range from approximately 20–40%. 24 The role of lateral sampling of the prostate was evaluated by Singh et al who showed that laterally directed cores were independent predictors of pathological features at prostatectomy. 25 …”
Section: Optimizing Prostate Biopsy In Clinical Practice – Core Numentioning
confidence: 99%
“…After 24 months (median) of follow-up, the median PSA was 0.9 ng/ml (range: 0.4-1.3 ng/ml). Despite the high PSA values compared with those diagnosed in the PZ, TZ PCa shows a less aggressive histological phenotype [29] ; at the same time, cancers found by directed biopsy cores do not reflect a dominant TZ lesion in almost 80% of cases at radical prostatectomy [30] .…”
Section: Discussionmentioning
confidence: 94%